Alkaline Phosphatase Activity of Plant Growth-Promoting Actinomycetes and Their Genetic Diversity Based on the phoD Gene - Muhammad Faiz Amri; Edi Husen; Aris Tjahjoleksono; Aris Tri Wahyudi (HAYATI Journal of Biosciences, 2022)
Actinomycete is one of the beneficial bacteria groups inhabiting rhizosphere soil. They can promote plant growth through various mechanisms. In the previous study we have isolated rhizosphere actinomycetes from maize rhizosphere with direct plant growth promotion characters. The aims of the present study were to analyze the ability of maize rhizosphere actinomycetes to solubilize phosphate, determine alkaline phosphatase activity, and study their genetic diversity based on phoD gene. Thirteen rhizosphere actinomycete isolates were able to solubilize phosphate at concertation range 55.84±2.27 mg/L to 144.48±5.71 mg/L. The activity of extracellular alkaline phosphatase was exhibited by all maize rhizosphere actinomycetes isolates in various level ranging from 0.08 mU/mL to 0.51 mU/mL. The phoD gene, one of the three homologous genes which encode alkaline phosphatases, was successfully detected in all isolates and identified as alkaline phosphatase D of Streptomyces spp. The partial phoD sequences of the isolates were located within metallophosphatase domain of alkaline phosphatase D. Alignment analysis showed that the deduced amino acid sequences of PhoD were mostly conserved in the isolates and Streptomyces spp. Essential residues involved in the active core arrangement of PhoD which binds metal ion cofactors were conserved. Constructed phylogenetic tree showed that the isolates were divided into two groups within PhoD cluster. PhoD of the isolates and Streptomyces spp. had closer relationship to purple acid phosphatase compared to other homologous PhoA and PhoX which form separate cluster. Generated three-dimensional structure model of partial PhoD had high similarity to alkaline phosphatase D of Bacillus subtilis (2YEQ) and showed overlapping structure based on super-positioning analysis.